Design for disassembly of adhesively bonded joints - Caglar, Hasan (Nanyang Technological University, 2023)
Adhesive bonding is a very promising joining technology for structural applications in aerospace, automotive and wind energy to realize complex multi-material geometries with, low-cost and weight penalties. Currently, there is a growing economic and environmental demands for glass fiber reinforced polymer (GFRP) and carbon fiber reinforced polymer matrix (CFRP) composite materials. However, when the composite adherend materials are required to be separated for repair or remanufacturing, the debonding process should not damage the composite materials. Depending on the damage level, the materials become suitable for one of the methods in the waste treatment hierarchy. If debonding on-demand techniques are developed to prevent damage, the materials will end up with the most preferred waste treatment option (i.e. prevention). In this predominantly experimental thesis, three competing strategies were employed to debond the adhesively bonded composite or composite/metal joints. Basically, the basic principle employed here is by increasing the temperature of the adhesive, the lap shear strength for debonding was reduced, thereby mostly achieving failure without damage so that the adherends can be reusable. The adherends are surface treated for effective bond strength. The debonding efficiency is measured in terms of percentage reduction in the lap shear stress under single lap joint (SLJ) configuration. Post-mortem analysis of joints was carried out by examining the remaining adhesive residue and light fiber-tearing on the surfaces. Further, the shear and peel distributions along the overlap region are obtained using analytical and numerical approaches. Firstly, the adhesive bondline was modified by interleaving three different carbon fiber veils which enable Joule heating of the adhesive system by applying an external voltage to the veils. GFRP adherends were bonded using two layers of epoxy film adhesive with/without interleaving carbon fiber veils to compare their effects on the joint. Joule heating characteristics of the materials were investigated experimentally. The Joule heating temperature measurements are compared with coupled thermal-electric based finite element method and Machine Learning (ML) solutions. Thermomechanical debonding of modified adhesive joints via a local Joule heating exhibited good debonding characteristics such as low force and time requirements as well as no fiber-tearing on the surface of the adherends and no bending of adherends. Secondly, thermally expandable particles (TEPs) were used to functionalize the adhesive bondline. Sandblasting and plasma surface treatments were also examined and compared in terms of their effects on the bonding and debonding of the adhesively bonded GFRP joints. The FTIR analysis of epoxy-TEP composites indicated no chemical interactions. TEPs inclusion has slightly changed the glass transition temperature (Tg) of epoxy adhesive. TMA analysis unveiled that TEPs lose the ability to expand permanently above maximum expansion temperature (~145oC) due to bursts and/or diffusion of gas through a thin shell. Increment in TEPs content up to 50 wt.% escalated the maximum dimension change in the epoxy adhesive remarkably. DMA and TGA analysis pointed out no major change in storage modulus and weight loss when GFRP was heated up to 170oC. The debonding efficiency for the joints with the TEP at 145oC is marginal when measured under SLJ configuration with the adhesive failure mode (except 15 wt.% TEPs joint configuration had mixed failure). Finally, iron oxide (Fe3O4) particles were incorporated into epoxy adhesive to enable induction heating of dissimilar joints. The dissimilar joint configurations were made of CFRP/Ti-6Al-4V and GFRP/Ti-6Al-4V by adding different Fe3O4 contents (0 wt.%, 2 wt.%, 5 wt.% and 10 wt.%). Herein, the thermomechanical properties of the Fe3O4 particles modified epoxy are measured. The storage modulus of neat epoxy decreased by more than 20% at room temperature after the addition of Fe3O4 particles. The thermal diffusivity of the neat epoxy was increased by more than 20% with the addition of Fe3O4 particles. CFRP/Ti-6Al-4V joints resulted in higher lap shear strength results with the incorporation of Fe3O4 particles while only 5 wt.% Fe3O4 added GFRP/Ti-6Al-4V joints showed higher lap shear strength at room temperature than neat epoxy joint configuration. DIC analysis indicated peel strain is dominant during the lap shear strength tests. GFRP and CFRP adherends had more epoxy residue after the tests which implies better adhesion of epoxy to the composite surfaces than Ti-6Al-4V surfaces. Sandblasted regions of Ti-6Al-4V showed enhanced electromagnetic induction heating characteristics compared to untreated regions. The time of failure of CFRP joints was shorter than GFRP joints. Thicker GFRP joints required more time to fail than thinner GFRP joints.